Le conflit armé dans le Territoire de Beni à l’épreuve du statut juridique des Forces Démocratiques Alliées, ADF en sigle - Bwamela , Jean-Claude Angel Likuya; Otemikongo , David Angalawe (IJRDO - Journal of Social Science and Humanities Research, 2022)
International humanitarian law fundamentally distinguishes between combatants and non-combatants. Everyone is aware that the Democratic Republic is the victim of acts of terrorism perpetrated by members of the Allied Democratic Forces, ADF in acronym. As parties to a conflict, ADFs assume a number of obligations under IHL. The members of this armed group benefit from the guarantees provided for by IHL in the context of their direct participation in hostilities but also when they are hors de combat due to injury, illness or detention.The main difficulty concerning this non-State armed group is that the States did not wish to confer on them a true combatant status under humanitarian law and particularly in non-international armed conflicts. Their status is therefore hybrid and remains largely covered by the national law of the State against which they are fighting. Developments in international criminal law and customary international humanitarian law have broadened the scope of their international rights and obligations.